Potencial energético da madeira e carvão vegetal de angico vermelho (Anadenanthera peregrina) jovem - Souza, Camilla de Oliveira (2018)
The objective of this work was to evaluate the energy potential of the wood and charcoal of the species Anadenanthera peregrina from experimental planting, planted in five spacings and carbonized in two different marches. For this, three trees, approximately 5 years old, were evaluated by planting spacing (3x2, 3x3, 4x3, 4x4, and 5x5 m). Five discs of the base were extracted per tree; of one disc was made the determination of the properties of the wood and four discs were transformed into charcoal in two carbonization marches (M1: heating rate of 1.67ºC and M2: 0,83ºC min-1 ), for later determination of the properties of the charcoal. The planting spacing did not influence the properties of angico wood, except total extractives, but had a significant effect on the properties of charcoal; the best parameters observed in plant spacing 3x3 m. The carbonization marches influenced the properties of charcoal, the best marche was M2. But, wood and charcoal had a high ash content, suggesting future analyzes to verify if there is a decrease of this variable over the years. There was interaction of the planting spacing with the carbonization marches for the ash content, relative density, energy density, yields in pyroligneous liquid and non condensable gases. The lignin content of the wood correlated positively with the relative density of the charcoal and the extractive content with the ash content of the charcoal.